TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWA - Mawarda Hatmanti, Nety (Jurnal Ilmiah Kesehatan, 2015)
Stress can made abnormal of reproduction system expecially cycle of menstruate. Stress can lead to serious physical illness. Stress in student may influence cycle of menstruate. If this condition continue, can made the women to infertile. This study is cross sectional design. The population were student in Program Studi S1 Ilmu Keperawatan Medicine Faculty of Airlangga University. Samples were recruited using consecutive sampling, and there were 57 samples who met the inclusion criteria. The observed variables were stress level and cycle of menstruate in fertile age student. Data were collected by questionare and observe. Then, data analyzed using Spearman Rank Correlation (p=0,000). The result showed that 26 students (46%) had moderate stress, 31 students (54%) had severe stress. The analyze of cycle menstruate showed that 34 students (60%) had cycle menstruate abnormal and 23 students (40%) had cycle menstruate normal. By using analysis non parametric, Spearman?s Rank Correlation the result showed that value correlation (r) = 0,464. It is mean that there is enought correlation between stress level and cycle of menstruate in fertile age student. Based on the conclution, we suggested to promote this information to the student about stress management. So, the cycle menstruste can normal.